Analisis Pemberian ASI Eksklusif di Puskesmas Tanjung Agung Kecamatan Baturaja Barat Kabupaten Ogan Komering Ulu - Ramayani; Chairil Zaman; Ali Harokan (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Breastfeeding is a food that contains and provides all the nutrients needed by babies in the early period of life. This study aims to determine what factors were associated with exclusive breastfeeding for breastfeeding mothers at the Tanjung Agung Health Center, Baturaja Barat District, OKU Regency 2022. The quantitative research method with the research design was Cross Sectional. The population in this study were mothers who had toddlers in the working area of ??the Tanjung Agung Health Center, Baturaja Barat District, OKU Regency 2021. The sampling method in this study used the accidental sampling technique. The number of samples in this study were 88 respondents. Data collection by using a questionnaire. The results of statistical test analysis using the chi-square test showed that there was a significant relationship (p value < 0.05) for knowledge (p value 0.019), parity (p value 0.024), family support (p value 0.014). There is no relationship between age (p value 0.840), availability of facilities (p value 0.55) and the role of officers (p value 0.63). From the results of multivariate analysis, it was found that the dominant factor in exclusive breastfeeding for breastfeeding mothers at Tanjung Agung Health Center in 2022 was family support (p value 0.017) (OR 0.266). From this research, it is hoped that the Puskesmas will provide information and support to mothers in exclusive breastfeeding.